Analisis Pengaruh Variasi Muatan Kendaraan dan Penumpang terhadap Stabilitas Kapal KM. Kirana III - Ari Purnama Dewa; Sutini .; Mu'izzadin Wa'adulloh (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
Ship stability is one of the important aspects that determine safety in shipping, especially on passenger ships and vehicles such as KM. Kirana III. This study aims to analyse the effect of variations in vehicle and passenger loads on the centre of gravity (CG) and metacentric height (GM). The research method used is quantitative analysis with stability calculations based on variations in vehicle and passenger load conditions, then compared with safety criteria set by the International Maritime Organisation(IMO). The calculation results show that the greater the vehicle load, especially when positioned higher or unevenly distributed, the greater the KG value (distance of th centre of gravity from the keel). The KG (Centre of Gravity Height from the Keel) for all voyage trips ranged between 5.57 – 5.71 metres. Changes in KG values were influenced by vehicle load distribution and passenger numbers, although the fluctuations were relatively small. This condition reduced the vessel's ability to return to an upri ht position, thereby decreasing vessel stability. The GM value (Metacentric Height) was obtained in the range of 1.19–1.33 m, while the GOm value (GM after Free Surface Effect) is in the range of 0.94–1.06 m. Both values remain positive, meaning the vessel is in a stable condition during each trip.variations in passenger numbers, especially those placed on the upper deck, reduce the GM value due to an increase in the centre of gravity. The combination of heavy vehicle loads and large numbers of passengers has proven to be the most risky in terms of reducing ship stability, although the GM value remains within safe limits if the load distribution is balanced. Placing heavy vehicles in the central deck area with balanced left-right distribution is the optimal configuration capable of maintaining a positive GM value. This study emphasises that monitoring the distribution of vehicle and passenger loads is crucial for maintaining vessel stability. These results can serve as a reference for vessel operators and shipping companies in developing safe and efficient loading strategies.